Knowledge about Worms in Primary 1 School - Napitupulu, David Sumanto; Pane, Jagentar Parlindungan; Simorangkir, Lindawati (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Student’s knowledge of worms is the result of student’s perceptions about worm infections and the process of how these worms can cause disease. Primary school student can be the main target for worm parasites because they often play in the dirt. The aim of this research was to determine the knowledge of Primary 1 school student about worms. This research method is called descriptive research, with a sample size of 40 participants and using total sampling. The results of the study found that the participants’knowledge about worms was 62,5% in the good category, 25% in the sufficient category and 12,5% in the poor category. Participant’s knowlegde was generally categorized as good due to the influence of teacher education at schooland assistance from the community health centers in administering worm medicine once every 6 months. Participants’knowledge about worms in general is good.